Neuroprotective Potential of Pyranocoumarins from Angelica gigas Nakai on Glutamate-Induced Hippocampal Cell Death - Nguyen Khoi Song Tran; Tuy An Trinh; Jaesung Pyo; Chang Geon Kim; Jae Gyu Park; Ki Sung Kang (MDPI AG, 2023)
Chronic neurodegenerative diseases are typically associated with oxidative stress conditions leading to neuronal cell death. We aimed to investigate the neuroprotective effect of three pyranocoumarins (decursin, decursinol angelate, and decursinol) targeting oxidative stress factors. Decursin (also known as dehydro-8-prenylnaringenin) is a prenylated coumarin compound consisting of a coumarin ring system with a prenyl group attached to one of the carbons in the ring. As a secondary metabolite of plants, pyranocoumarin decursin from Angelica gigas Nakai presented protective effects against glutamate-induced oxidative stress in HT22, a murine hippocampal neuronal cell line. Decursinol (DOH) is a metabolite of decursin, sharing same coumarin ring system but a slightly different chemical structure with the prenyl group replaced by a hydroxyl group (-OH). In our findings, DOH was ineffective while decursin was, suggesting that this prenyl structure may be important for compound absorption and neuroprotection. By diminishing the accumulation of intracellular reactive oxygen species as well as stimulating the expression of HO-1, decursin triggers the self-protection system in neuronal cells. Additionally, decursin also revealed an anti-apoptotic effect by inhibiting chromatin condensation and reducing the forming of annexin-V-positive cells.